“They Have to Combine the Future of the University and Their Own Future”: OpenCourseWare (OCW) Authoring as an Academic Practice in Spain - Villar-Onrubia, Daniel (International Review of Research in Open and Distributed Learning, 2022)
This study looks at OpenCourseWare (OCW) in Spain, a country where most public universities have tried to promote that particular model of open educational resources (OER) provision among academics. Using three universities with varying levels of OCW activity as a case study, this article examines key drivers behind the implementation of OCW initiatives and unpacks what it means, as an academic practice, to engage in OCW authoring. Following a qualitative case study approach and a multi-methods design, this study offers a basis for theoretical generalisations that can be useful for understanding similar dynamics taking place within different organisational contexts in Spain and beyond. The findings reveal a major disconnect between the drive to implement OCW initiatives in Spain and actual opportunities for academics to engage with them as part of their work. The author concludes that the extrapolation of a highly prescriptive model of OER provision into institutional realities different from the context where it was originally devised—in this case, the Massachusetts Institute of Technology in the United States—is rather problematic. The article also provides some recommendations to university leaders and policy makers, encouraging the creation of alternative models that are mindful of the institutional and cultural specificities of their own contexts and also to take into consideration the social and material realities of the communities they aim to provide with lifelong learning opportunities.